МОРФОЛИТОДИНАМИЧЕСКИЙ АСПЕКТ ЭКОЛОГИИ ПОБЕРЕЖЬЯ БАЛТИЙСКОГО МОРЯ - Богданов Н.А. (My University, 1993)
A conflict between technogenic factor and environmental characteristics of the Baltic coastal zone in Lithuania in the late 19th — early 20th centuries resulted in irreversible degrading of coastal lithodynamic system and formation of morpholithodynamic anomalies. The dimensions of ecologically endangered zone of coast and offshore slope exceed the area of conflict by an order of magnitude. For half a century the sea floor erosion rate averaged to 1,4 10**6 cub. m per year over a 40 km stretch. Average rate of the scarp retreat during 1905 to 1990 equalled to 0.8 to 2,5 m per year (or 12 to 38 thous. cub. m per year), the mean height of the scarp is about 3 m over a length of 5 km. During the 1980ies the rate of coast retreat increased from 0,7—1,7 to 3—4 m per year. Investigations into morpholithodynamics should be a priority when studying ecological problems of the sea coasts.